DESKRIPSI TEKNIS PENGENDALI TEMPERATUR INDUSTRI SEBAGAI BAGIAN DARI SISTEM REGULASI TEMPERATUR - Tadeus, Dista Yoel; Setiono, Iman (Gema Teknologi, 2018)
Dista Yoel Tadeus, Iman Setiono, in this paper explain that temperature regulation is one of the most important needs for the industry. Lots of processes and production are carried out under certain temperature conditions and free from interference. Industrial temperature controller is one of the basic equipment to meet these needs. On the market there are various types, specifications, and brands of temperature controllers, but have similarities with one another mainly lies in the basic functions of temperature regulation capabilities. This article describes the background of industrial temperature controllers principal, also covers control concepts, basic controller configurations, control methods, actuator equipment support, and examples of sensor parameter settings and controls on the Autonics TC4S series temperature controllers.